KEMEMPUAN TETAS TELUR DAN VIABILITAS DAY OLD CHICK (DOC) AYAM HASIL PERSILANGAN - Laya, Nibras; Gubali, Syukri; Dako, Safriyanto (Gorontalo Journal of Equatorial Animals, 2025)
The study is aimed to investigate Hatchability of eggs, and Viability of Day Old Chick (DOC), the result of  hybridization between  native chicken and broiler  chicken. The chickens consist of 3 male native chickens and 30 female broiler chickens.  The Hybridization is conducted through artificial insemination. The observed variables are fertility, Hatchability and Viability of Day Old Chick, The data  that have been collected are analyzed descriptively by calculating the mean, deviation standard, and coefficient of variation. Findings reveal that the mean score of fertility is 78,95%, hatchability of egg is 56,97%, and the viability is 90,85%. Based on result and discussion, it can be concluded that the fertility, hatchability and viabilityof Day Old Chick (DOC)  are higher than native chickens. Keywords:Hatchability, and Viability  of DOC, Hybridization